Proper pertussis vaccination will probably not increase vaccination coverage: a case–control study. (2019) - Solano, R.; Sanchez-Callejas, A. V.; Alvarez-Ibañez, M. I.; Sandiumenge-Durán, M.; Fernández-San-Martín, M. I.
Abstract: Vaccination coverage (VC) against pertussis can increase when management practices and policies at primary care centres (PCCs) are reinforced. From 2011 to 2015, we performed a case–control study to evaluate VC among pertussis patients treated at PCCs in Barcelona, Spain. We recorded pertussis in patients from 8- to 16-year-olds at 52 PCCs. Pertussis cases had laboratory diagnostic and controls were healthy outpatients visiting the same facility for reasons other than cough. DTaP/dTap VC was recorded as either proper vaccination status (five doses recorded) or improper vaccination status (<5 doses recorded). We used a logistic regression model to estimate OR and 95% CI. We included 229 cases and 576 controls. VC was higher in cases (mean 5.01, s.e. : 0.57) than in controls (4.89, s.e. : 0.73). Around 69% of the cases had received DTaP primary immunisation after 2–5 years and 31.4% of cases had the dTap booster immunisation after 7–10 years. The 87% of children 5–9 years were properly vaccinated. We found no protection from becoming ill among properly vaccinated children (OR 1.87; 95% CI 1.22–2.85). The highest VC was observed in patients with confirmed pertussis, which was likely due to a more exhaustive follow-up of the VC in these patients. Being properly vaccinated against pertussis will probably not increase VC.